2012
DOI: 10.1039/c2dt30448a
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of carbon dioxide and related small molecules by a bifunctional frustrated pyrazolylborane Lewis pair

Abstract: The bifunctional frustrated Lewis pair 1-[bis(pentafluorophenyl)boryl]-3,5-di-tert-butyl-1H-pyrazole (1) was employed for small molecule fixation by reaction with carbon dioxide, paraformaldehyde, tert-butyl isocyanate, tert-butyl isothiocyanate, methyl isothiocyanate and benzonitrile, affording the adducts 3-8 as zwitterionic, bicyclic boraheterocycles. Treatment of 1 with tert-butyl isocyanide gave the isocyanide-borane complex 9, whereas the zwitterionic alkynylborate 10 was formed by C-H bond activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 69 publications
5
50
0
1
Order By: Relevance
“…Moreover,t he NOCV (natural orbital for chemical valence) [28] extension of the EDA method has been used to further partition the DE orb term. Moreover,s imilar reactionp rofiles were computed for the more realistic geminal B/N FLP 1-[bis(pentafluorophenyl)boryl]-3,5-di-methyl-1H-pyrazole [12] and B/P FLP Me 2 PCH 2 BPh 2 , [13] which provides further support fort he model compounds that are consideredh erein (see the SupportingI nformation, Figure S1). Figure 1s hows the computed reaction profile for ar epresentative hydrogenation reactiont hat involves zwitterion 2f (R = C 6 F 5 )a nd methanimine (6).…”
Section: Energyd Ecomposition Analysismentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover,t he NOCV (natural orbital for chemical valence) [28] extension of the EDA method has been used to further partition the DE orb term. Moreover,s imilar reactionp rofiles were computed for the more realistic geminal B/N FLP 1-[bis(pentafluorophenyl)boryl]-3,5-di-methyl-1H-pyrazole [12] and B/P FLP Me 2 PCH 2 BPh 2 , [13] which provides further support fort he model compounds that are consideredh erein (see the SupportingI nformation, Figure S1). Figure 1s hows the computed reaction profile for ar epresentative hydrogenation reactiont hat involves zwitterion 2f (R = C 6 F 5 )a nd methanimine (6).…”
Section: Energyd Ecomposition Analysismentioning
confidence: 64%
“…The selected transformations were chosen to quantitatively assess the influenceo fb otht he substituents at the FLP and the nature of the multiple bond on the transformation.E ven thoughi th as been found that related geminal aminoborane species (R 2 NCH 2 BAr 2 )f orm head-to-tail dimers and oligomers under certainc onditions, [11] the studied systems can still be considered as modelc ompounds of more realistic geminal B/N [12] or B/P [13] FLPs. To this end, we focused on the processes that involves the most representative FLPs (i.e.,t hose that have feasible H 2 activation barriers) and differentm ultiple bonds, which includes either polar (O=C, N=C) or nonpolar (C=C, CC) bonds( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Other B/P‐based FLPs gave one of the two isomers indicating the importance of steric influence . The pyrazolylborane 3,5‐ t Bu 2 C 3 N 2 H–B(C 6 F 5 ) 2 , a highly effective B/N‐based FLP, reacted with t Bu‐NCO and Me‐NCS to yield the C=O and C=N products consistent with a preferred interaction of the hard B atom with the hard Lewis bases O and N . In contrast, the sterically more demanding isothiocyanate t Bu–NCS yielded the C=S activation product.…”
Section: Resultsmentioning
confidence: 99%
“…Tamm and co-workers [100] prepared the intramolecular N/B FLP based on the pyrazolyl-borane (C 3 H t Bu 2 N 2 )B(C 6 F 5 ) 2 and showed binding of CO 2 to give, in a strongly exothermic reaction, (C 3 H t Bu 2 N 2 )B(C 6 F 5 ) 2 (CO 2 ) (114). The Uhl group has also prepared intramolecular Al/P systems for CO 2 capture by hydroalumination of the alkynyl phosphine by R 2 AlH affording Mes 2 PC(CHR')AlR 2 [103] The corresponding reactions of bis-boranes and phosphines with CO 2 was also probed.…”
Section: Hidden Flpsmentioning
confidence: 99%